PENGARUH STRUKTUR KEPEMILIKAN TERKONSENTRASI DAN KARAKTERISTIK KOMITE AUDIT TERHADAP TINGKAT KEINFORMATIFAN LABA - Muhammad Ibnu Hakim; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
This research aimed to examine the effect of concentrated ownership structure and the audit committee characteristics on the earnings informativeness, as well as examine the negative effect of concentrated ownership on the relationship of audit committee characteristics with earnings informativeness. Concentrated ownership in this research is based on the percentage shares of ownership in a company. Audit committee characteristics consist of independent, non- financial characteristic, financial expertise, and legal expertise. Control variables in this research are the size of the company, leverage, and market-to-book ratio. This research is based on research conducted by Yeh and Woidtke (2013) and Wawo (2010) with modifications on the variables and sample. This research is modified by making concentrated ownership variable as moderating variable to examine the negative effect of it on the relationship between audit committee characteristics and earnings informativeness. In accordance with Yeh and Woidtke (2013), earnings informativeness is proxied by relationship between earnings and cumulative abnormal returns (CAR).The research used secondary data from the annual reports of all companies listed on the Indonesian Stock Exchange (IDX) from 2010 to 2013. Sampling method used in this research was purposive sampling. A total sample of 164 companies data were used in analysis. The data is analyzed using multiple linear regression analysis.The results of this research indicate that concentrated ownership negatively affects earnings informativeness and independence of audit committees positively affects earnings informativeness. Concentrated ownership may reduce the positive relationship between independence of the audit committee and earnings informativeness. Nevertheless, the results of this research found no effect of the characteristics of non-financial characteristic, financial expertise, legal expertise on the earnings informativeness. Concentrated ownership does not moderate the relationship of these three characteristics with earnings informativeness.